High frequency diffraction of cylindrical waves by perfectly conducting successive step discontinuities - Turetken, B.; Alkumru, Ali; Buyukaksoy, A.; Kustepeli, A. (IEEE, 2006)
The diffraction of high frequency cylindrical electromagnetic waves by step discontinuities is investigated rigorously by using the Fourier transform technique in conjunction with the mode matching method. The hybrid method of formulation gives rise to a scalar Wiener-Hopf equation of the third kind, the solution of which contains infinitely many constants satisfying infinite systems of linear algebraic equations.
11th International Conference on Mathematical Methods in Electromagnetic Theory -- JUN 26-29, 2006 -- Kharkiv, UKRAINE
Keywords: Rectangular Impedance Cylinder; Plane; Scattering